2022
DOI: 10.1371/journal.pone.0271378
|View full text |Cite
|
Sign up to set email alerts
|

Level of dietary adherence and determinants among type 2 diabetes population in Ethiopian: A systemic review with meta-analysis

Abstract: Background The beneficial effect of the dietary practice is significant reduction in the risk of developing diabetes related complication. Dietary practice among type 2 diabetes is not well-implemented in Ethiopia. Up to now, in the nation, several primary observational studies have been done on dietary adherence level and its determinants among type 2 diabetes. However, a comprehensive review that would have a lot of strong evidence for designing intervention is lacking. So, this review with a meta-analysis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 67 publications
1
4
0
Order By: Relevance
“…29 However, as observed in our review, the prevalence of adherence to T2DM treatment in Brazil is not ideal for any of the three pillars. In a systematic review with a meta-analysis conducted in Ethiopia, 30 the combined prevalence of diet adherence by people with T2DM was 41.05% (95% CI: 34.86-47.24, I 2 = 93.1%), showing similarity with this meta-analysis carried out in Brazil, which can be explained by the fact that low income and lower education were determinants of adherence in both countries. In a meta-analysis carried out in the United States, 31 the combined prevalence of adherence to physical activity was 77% (95% CI= 0.68; 0.84), which is higher than that performed with Brazilians.…”
Section: Risk Of Biassupporting
confidence: 64%
See 3 more Smart Citations
“…29 However, as observed in our review, the prevalence of adherence to T2DM treatment in Brazil is not ideal for any of the three pillars. In a systematic review with a meta-analysis conducted in Ethiopia, 30 the combined prevalence of diet adherence by people with T2DM was 41.05% (95% CI: 34.86-47.24, I 2 = 93.1%), showing similarity with this meta-analysis carried out in Brazil, which can be explained by the fact that low income and lower education were determinants of adherence in both countries. In a meta-analysis carried out in the United States, 31 the combined prevalence of adherence to physical activity was 77% (95% CI= 0.68; 0.84), which is higher than that performed with Brazilians.…”
Section: Risk Of Biassupporting
confidence: 64%
“…Some authors observed that low income, 11,14,15,19 low educational level and multimorbidities were associated with poor adherence to the diet. 11,12,14,17 The meta-analysis by Abate et al 30 showed that income and education were determinants of this low adherence. The authors observed that individuals with greater monthly financial availability had a more balanced diet, as it is possible that they are more likely to acquire healthy foods.…”
Section: Risk Of Biasmentioning
confidence: 99%
See 2 more Smart Citations
“…Someone with a higher level of education can make better judgments and decisions about choosing a healthy diet and eating behavior [18]. In line with this theory, research regarding the factors that influence diet adherence in T2DM patients at the Kedungmundu Public Health Center in Semarang City shows that there is a relationship between education level and adherence to diet in T2DM patients as evidenced by the results of the chi-square test obtained p = 0.046 [19].…”
Section: Resultsmentioning
confidence: 89%